Pengecualian Sengketa Tanah Dalam Tata Cara Gugatan Sederhana (Small Claim Court) - A. Irfan Suandy; Andi Risma; Ma'ruf Hafidz (Journal of Lex Generalis (JLG), 2021)
Tujuan penelitian menganalisis alur proses penyelesaian Gugatan Sederhana sesuai dengan Perma No 2 Tahun 2015 jo. Perma No 4 Tahun 2019. Metode Penelitian menggunakan penelitian hukum yuridis normatif. Hasil penelitian bahwa Alur dan tahapan-tahapan hukum acara dalam penyelesaian gugatan sederhana diatur dalam Pasal 5 Perma No. 2 Tahun 2015 jo. Perma No. 4 Tahun 2019 meliputi: pendaftaran gugatan, pemeriksaan kelengkapan gugatan sederhana, penetapan hakim dan penunjukan panitera pengganti, pemeriksaan pendahuluan, penetapan hari sidang dan pemanggilan para pihak, pemeriksaan sidang dan perdamaian, pembuktian, dan putusan. Melalui Perma No. 2 Tahun 2015 jo. Perma No. 4 Tahun 2019, penyelesaian gugatan sederhana dapat mewujudkan asas cepat yang terlihat dari ketentuan-ketentuan yang ada didalamnya seperti penyelesaian gugatan sederhana diselesaikan dengan batas waktu maksimal 25 hari terhitung sejak dimulainya sidang pertama, asas sederhana terlihat dari adanya ketentuan Pasal 1 angka 1 PERMA No. 2 Tahun 2015 jo. Perma No. 4 Tahun 2019. The research objective was to analyze the flow of the simple lawsuit settlement process in accordance with Perma No. 2 of 2015 jo. Perma No. 4 of 2019. The research method uses normative juridical legal research. The results showed that the flow and stages of procedural law in the settlement of a simple lawsuit are regulated in Article 5 Perma No. 2 of 2015 jo. Perma No. 4 of 2019 includes: lawsuit registration, examination of simple lawsuit completeness, appointment of judges and appointment of substitute clerks, preliminary examinations, determination of trial days and summons of parties, trial and reconciliation examinations, evidence, and verdicts. Through Perma No. 2 of 2015 jo. Perma No. 4 of 2019, the settlement of a simple lawsuit can realize the principle of speed which can be seen from the provisions contained therein such as the settlement of a simple lawsuit is completed with a maximum time limit of 25 days from the start of the first trial, the simple principle can be seen from the existence of the provisions of Article 1 number 1 PERMA No. 2 of 2015 jo. Perma No. 4 of 2019..